An unexpected case report of epidermoid cyst at the oculomotor nerve: mimicking a common cyst on MRI - He, Yuhao; Zhang, Sunfu (Frontiers in Endocrinology, 2023)
Intracranial epidermoid cysts are benign lesions and are rarely seen in clinical practice. Owing to similarities in imaging findings to those of common cystic lesions, the preoperative diagnosis is rendered challenging. Here we present a case report of an epidermoid cyst at the right oculomotor nerve, which was initially misdiagnosed as a common cyst. A 14-year-old female child was admitted to our department due to a previous magnetic resonance imaging scan of a cystic lesion on the right side of the saddle which was suspected to be an oculomotor nerve cyst. In our department, this patient underwent complete surgical resection of the tumor, and the pathology results revealed an epidermoid cyst. This is the first study that reported an epidermoid cyst at the right oculomotor nerve entering the orbit, mimicking a common cyst in imaging. We hope that this study would allow clinicians to consider this type of lesion as a differential diagnosis. Moreover, we suggest that specific diffusion-weighted imaging scan should be performed to aid in the diagnosis.